KESEJAHTERAAN DALAM PERSPEKTIF MAQASHID SYARIAH PADA KARYAWAN BADAN AMIL ZAKAT DAN LEMBAGA AMIL ZAKAT DI KOTA SURABAYA - Annisa Dinar Rahman; Siti Inayahtul Faizah (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This study aims to determine the welfare of employees at the Amil Zakat Agency and the Amil Zakat Institution in Surabaya if it is reviewed through the perspective of maqashid sharia. This study uses a qualitative case study approach with descriptive analysis techniques through interviews, documents, and direct observation. The scope of this research focuses on employees of the Amil Zakat Agency and the Amil Zakat Institution. The results of this study are economic conditions in terms of income received by employees of the Amil Zakat Agency and the Amil Zakat Institution are sufficient. This economic situation can be seen from the amount of income received per month, fulfillment of needs, and assets owned. Fulfillment of welfare for employees at the Amil Zakat Agency and the Amil Zakat Institution can be said to be prosperous. This welfare can be seen from the maqashid sharia indicator used in this study, which is maintaining religion, nurturing the soul, nurturing the logics, raising offspring, and maintaining wealth, both the Amil Zakat Agency and the Amil Zakat Institution have received and benefited from the facilities provided by the institution , such as the existence of health benefits (BPJS).Keywords: Employee welfare, Maqashid Syariah, Amil Zakat Agency, Amil Zakat Institution